Psychology - Dennis Coon (Thomson/Wadsworth, 2008)
A psychology text that you'll actually want to read! PSYCHOLOGY: A JOURNEY is guaranteed to spark your curiosity, insight, imagination, and interest. Using the proven SQ4R (Survey, Question, Read, Recite, Relate, and Review) active learning system to help you study smarter, Coon leads you to an understanding of major concepts as well as how psychology relates to the challenges of everyday life. Each chapter of this book takes you into a different realm of psychology, such as personality, abnormal behavior, memory, consciousness, and human development. Each realm is complex and fascinating, with many pathways, landmarks, and detours to discover. Take the journey and find yourself becoming actively involved with the material as you develop a basic understanding of psychology that will help you succeed in this course and enrich your life